2015
DOI: 10.1103/physrevb.91.195420
|View full text |Cite
|
Sign up to set email alerts
|

Electron waiting times in coherent conductors are correlated

Abstract: We evaluate the joint distributions of electron waiting times in coherent conductors described by scattering theory. Successive electron waiting times in a single-channel conductor are found to be correlated due to the fermionic statistics encoded in the many-body state. Our formalism allows us also to investigate the waiting times between charge transfer events in different outgoing channels. As an application we consider a quantum point contact in a chiral setup with one or both input channels biased by eith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 58 publications
(123 reference statements)
1
82
0
Order By: Relevance
“…[2][3][4][6][7][8][9][10][11]13,14 The question which we discuss in this paper is the following. When an electron transfers through a molecular junction, is there exists a correlation between waiting times for successive electron tunneling or they are statistically independent?…”
mentioning
confidence: 99%
“…[2][3][4][6][7][8][9][10][11]13,14 The question which we discuss in this paper is the following. When an electron transfers through a molecular junction, is there exists a correlation between waiting times for successive electron tunneling or they are statistically independent?…”
mentioning
confidence: 99%
“…The physical interpretation of this RTD (25) depends on the definition of L 0 , which is determined by the splitting of the total Liouvillian into monitored quantum jumps and the generator for background quantum dynamics. We will consider two cases -the electron and an electron tunnelling.…”
Section: S/d 21mentioning
confidence: 99%
“…The initial increase of the residence time at small temperature, so that electrons spend longer time in the nanoscale system before jumping out to the drain, is due to blocking of the available states in the drain electrode by spreading the thermal Fermi-Dirac distribution. As the temperature increases further, the electronic population of the nanoscale system starts to grow and the intermediate quantum (25), they are involved in the calculations of the normalisation: the RTD is normalised to unity if it is integrated over time from 0 to ∞ and is summed over all possible secondary quantum jumps. This is reflected in the monotonic decrease of average residence times at larger temperature.…”
Section: S/d 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Dasenbrock et al [3] have shown the correlation of subsequent waiting times in the coherent transport through a quantum point contact described within the scattering matrix formalism. Here the study is extended to the case of quantum dots.…”
Section: Introductionmentioning
confidence: 99%